2010
DOI: 10.3390/molecules15053391
|View full text |Cite
|
Sign up to set email alerts
|

Relaxant Effect of the Ethanol Extract of Helichrysum plicatum (Asteraceae) on Isolated Rat Ileum Contractions

Abstract: Helichrysum plicatum (Turkish Helichrysum) has been used in folk medicine for the treatment of gastric and hepatic disorders. The aim of the present study was to examine the relaxant activity of an extract of H. plicatum flowers on isolated rat ileum. Segments of ileum of rats were suspended in an organ bath. Cumulative concentrations of H. plicatum ethanol extract induced a relaxant effect on spontaneous rat ileum contractions. H. plicatum extract caused a mean contractile response of 81.68 ± 6.17% (at a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Chemically, this species responsible for the therapeutic effects of the plant. H. plicatum polar extracts are reported to possess antimicrobial, antidiabetic, spasmolytic, nephroprotective, and antimutagenic activities [13,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, this species responsible for the therapeutic effects of the plant. H. plicatum polar extracts are reported to possess antimicrobial, antidiabetic, spasmolytic, nephroprotective, and antimutagenic activities [13,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of non-selective cation channels in the plasma membrane causes membrane depolarization and influx of calcium ions through voltage-dependent calcium channels. Another mechanism of the activation of contraction occurs due to the release of intracellular calcium 17,18 . The interactions of acetylcholine with muscarinic receptors in the intestinal smooth muscle induce a G protein-mediated signal transduction that increases cytosolic calcium ion concentration, depolarization and the contractions of the intestinal smooth muscle 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Different plant extracts usually mediate their spasmolytic action through blockage of Ca2+ influx. This indicates that the plant extract is preventing the increase of calcium ions and muscle tension 3 . This result is in agreement with the results of others which examined the effects of other plants on isolated smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Also essential oil, such as a-pinene, b-pinene exhibited relaxation effect on isolated rat ileum contractions 19 . These materials have been reported to exhibit calcium antagonist and anticholinergic activities 3 . Several studies in vitro and in vivo showed that those compounds can regulate disturbances of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation